CHINESE FAMILY EDUCATIONAL PATTERNS IN CULTIVATING ENTREPRENEURIAL SPIRIT: A THEMATIC ANALYSIS IN SURAKARTA - Abdurrahman, Afif; Sudira, Putu; Hidayati, Tuti; Rizki, Darlin; Dewi, Ayuana Kartika (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2025)
The entrepreneurial spirit within Chinese-Indonesian families has long been recognized as a factor in their economic resilience, yet the educational patterns that transmit this spirit across generations remain underexplored. This study aims to examine how family-based education fosters entrepreneurial character among Chinese youth in Surakarta, focusing on the interplay of cultural values, practical immersion, and adaptive strategies. The central research question asks: How do educational practices within Chinese-Indonesian families contribute to cultivating entrepreneurial spirit in the next generation? This research employs a qualitative approach using thematic analysis to interpret data gathered through in-depth interviews, observations, and documentation. The findings reveal three major themes: first, practical immersion as pedagogy, where children are engaged in family business tasks from an early age to internalize perseverance, discipline, and interpersonal competence; second, familial trust and solidarity as social capital, where kinship bonds and moral values of honesty, responsibility, and integrity sustain intergenerational continuity; and third, the negotiation of formal education, experiential learning, and technology, where families balance schooling with hands-on practice and cautiously integrate digital tools as both opportunities and risks. The study concludes that entrepreneurial education in Chinese-Indonesian families is not merely an economic strategy, but a cultural and ethical practice embedded in family life. Theoretically, this study shows that entrepreneurial spirit is socially enacted within kinship structures rather than taught solely in schools. Practically, the findings suggest that entrepreneurship programs can be strengthened through family-based approaches that emphasize early immersion, trust, ethics, and guided use of technology.